Nonlinear metamaterials for holography - Euclides Almeida (Nature Portfolio, 2016)
Phased metasurfaces have been extended to the nonlinear regime, enabling coherent generation, beam steering and lensing of light beams in one thin element. Here, Almeida et al. demonstrate a nonlinear multilayer metamaterial hologram generating images at the third harmonic frequency of the illuminating beam.